Psalm 85: Yearning for the restoration of the whole body - Coetzee, Johan H. (Old Testament Essays, 2009)
In this paper Psalm 85 is approached from the angle of embodied language. The embodied experiences of the poet are verbalised and metaphorised in terms of the societal body, the people of Israel in distress after their return from the Babylonian exile. The societal body of Israel, the role of "land" in the psalm, and the three-dimensional relationship between God, the people, and the land are analyzed in terms of the embodied rhetoric implemented by the poet in order to indicate how the embodied language expresses the yearning for whole-bodiedness by the returned exiles.
free